Political dynasties and poverty: Evidence from the Philippines - Mendoza, Ronald U (Archīum Ateneo, 2013)
One definition of political dynasties refers to members of the same family occupying elected positions either in sequence for the same position, or simultaneously across different positions. In the Philippines, poverty appears critically linked to the prevalence of political dynasties at the provincial level. Either poverty brings about political dynasties, or political dynasties fail to reduce, or even exacerbate, poverty. The dominant direction of causation is an empirical question. This study responds by analyzing a unique Philippine provincial-level dataset. It also uses an instrumental variable technique to deal with endogeneity issues, and develops novel metrics on political dynasties. The empirical findings suggest that poverty entrenches political dynasties, while there is less evidence that political dynasties exacerbate poverty.